2021
DOI: 10.3390/cancers13010144
|View full text |Cite
|
Sign up to set email alerts
|

NPM-ALK: A Driver of Lymphoma Pathogenesis and a Therapeutic Target

Abstract: Initially discovered in anaplastic large cell lymphoma (ALCL), the ALK anaplastic lymphoma kinase is a tyrosine kinase which is affected in lymphomas by oncogenic translocations, mainly NPM-ALK. To date, chemotherapy remains a viable option in ALCL patients with ALK translocations as it leads to remission rates of approximately 80%. However, the remaining patients do not respond to chemotherapy and some patients have drug-resistant relapses. It is therefore crucial to identify new and better treatment options.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 107 publications
1
11
0
Order By: Relevance
“…The diagnosis of PTCL is one of the most challenging among lymphomas and more often results in an inconclusive, inconsistent, or incorrect diagnosis. [19][20][21]32,33 Recently, novel therapeutic approaches have shown striking benefits in subgroups of PTCL, including brentuximab vedotin on CD301 PTCL, particularly ALCL 34 ; crizotinib in ALK1 ALCL 35,36 ; mogamulizumab in ATLL 37 ; HDACi and demethylating agents in AITL or T FH -PTCL 38 ; and possibly enasidenib in IDH2-mutant AITL. 39 Thus, accurate diagnosis may be important for patient treatment and in clinical trials of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PTCL is one of the most challenging among lymphomas and more often results in an inconclusive, inconsistent, or incorrect diagnosis. [19][20][21]32,33 Recently, novel therapeutic approaches have shown striking benefits in subgroups of PTCL, including brentuximab vedotin on CD301 PTCL, particularly ALCL 34 ; crizotinib in ALK1 ALCL 35,36 ; mogamulizumab in ATLL 37 ; HDACi and demethylating agents in AITL or T FH -PTCL 38 ; and possibly enasidenib in IDH2-mutant AITL. 39 Thus, accurate diagnosis may be important for patient treatment and in clinical trials of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for translocation events of NPM1, treatment has been associated with the elimination of the fusion protein directly. This includes anaplastic large-cell lymphoma with NPM1-ALK (anaplastic lymphoma kinase) and T-cell lymphoma with NPM1-TYK2 (tyrosine kinase 2) [ 58 , 59 ]. It must be noted that only a small proportion of patients who exhibit NPM1 mutations outside of AML can be found.…”
Section: Npm1 Mutations In Aml and Other Malignanciesmentioning
confidence: 99%
“…ALK TKI resistance can either be ALK-dependent or -independent with the former largely occurring due to mutations in ALK ( Figure 1 and Figure 4 ). These have been reported as either mutations in residues at the TKI binding site, or those that result in conformational changes that increase aberrant ALK activity [ 76 , 77 ]. Extensive studies of ALK-dependent resistance mechanisms in NSCLC [ 17 , 78 ] have identified numerous mutations which in some cases are specific to a certain ALK TKI and in others are ubiquitous amongst the ALK TKIs ( Table 1 ).…”
Section: Mechanisms Of Resistance To Alcl Therapymentioning
confidence: 99%